Kebangkitan Orang Mati (Daniel 12:1-4) - Frischa Nofrianti; Kevin Boris Anugrah Marbun; Herdiana Boru Sihombing M.Th (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In the Christian context, the resurrection of the dead is based on the resurrection of Jesus Christ after the crucifixion, which forms the basis of the Christian faith that all people will experience resurrection at the end of time to face the final judgment. In the Old Testament, death is understood as the separation between body and spirit. After we die, our bodies will decompose and become soil again while the spirit will leave our bodies for the afterlife, also known as Sheol. There is also a belief in the resurrection of the dead, which is the physical return of the body from the dead. This belief is reflected in books such as Daniel and Isaiah, which state that at the end of time, God will raise the dead to eternal life or eternal punishment. This concept of resurrection affirms the belief in divine justice and restoration, where each person will receive reward or punishment according to their deeds. In Christian theology, the resurrection of the dead provides hope for eternal life as well as complete redemption, and simultaneously reminds the faithful of the importance of living righteously and faithfully to God's teachings.